Epidemiological, spatial and temporal distribution of ophidism cases registered in the National Center for Epidemiology, Prevention and Control of Diseases (CDC-PERU) during the period 2010 – 2019 - Herrada, Gabriela (2021)
The objective was to describe the epidemiological, spatial and temporal distribution of ophidism cases registered in the National Center for Epidemiology, Prevention and Control of Diseases (CDC-PERU) during the period 2010-2019. For this, a descriptive observational study, which used the information of reported cases of ophidism at the national level, registered in the Virtual Health Situation Room, CDC - Peru. Information about region, year of occurrence, epidemiological week expressed in quartiles and four-month intervals, age group and sex of the injured person, was obtained. The information obtained was summarized using descriptive statistics and the association between variables was made using the Chi Square test. Information was collected from 22,564 reports of ophidism. The departments that registered the highest frequency of cases during the study period were Loreto (28.4%), San Martín (19.7%) and Ucayali (13.3%), which together accounted for 61.4% of the total notifications. Accidents in men (65.5%) were more frequent than in women (34.5%). According to age group, adults between 30-59 and 18-29 years old accounted for 64.7% of the total reported cases. In the first half of the year, which incorporates the first (week 1 to 13) and second (week 14 to 26) quartile, the majority of cases occurred (30.7 and 27.4%, respectively), which corresponds to 58.8%. The sustained presence of cases of ophidism over time requires accentuating prevention measures throughout the year, especially in areas where its presence was greater.